The potential contribution of the shipping sector to an efficient reduction of global carbon dioxide emissions - Nadine Heitmann; Sonja Peterson (Kiel Institute for the World Economy (IfW), 2012)
In this paper, we analyze how much the shipping sector could contribute to global CO2 emission reductions from an efficiency point of view. To do this, a marginal abatement cost curve (MACC) for the shipping sector is generated that can be combined with a MACC for conventional CO2 abatement in the production and consumption sectors around the world. These two MACCs are used to assess the following as regards the various global reduction targets: (a) what the maximum global cost savings would be that could be achieved by abating emissions in the shipping sector, (b) how much the shipping sector could contribute to abating emissions cost efficiently, and (c) what the potential additional costs of implementing a separate solution for the shipping sector would be. The focus is on the year 2020. We find that the shipping sector could always contribute to efficient global emission reductions and thus could always achieve global cost savings, but also that the size of the contribution and the size of cost savings depend heavily on the MACC case assumed, i.e., on how the existence of negative abatement costs is treated in a MACC, and on the reduction potentials and costs of measures assumed.
Keywords: Q52; Q54; Q58; 330; climate change; shipping sector; CO2 emissions; marginal abatement cost curve